A Case of Granulomatosis with Polyangiitis Diagnosed at Autopsy. Issue 2 (June 2017) - Pinckard, J. Keith
Herein is reported a case of granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis, diagnosed at forensic autopsy in an 83-year-old woman with a history of Alzheimer disease. Significant findings at autopsy were cardiac hypertrophy, nephroarteriolosclerosis, hemorrhagic lungs, and necrotizing granulomatous inflammation with vasculitis involving the lungs and kidneys. Semiquantitative immunofluorescence testing was positive for cytoplasmic antineutrophil cytoplasm antibodies at a titer of 1:40. An enzyme-linked immunosorbent assay for proteinase 3 was strongly positive at 134 units (reference range: positive greater than 30 units). The cause of death was therefore determined to be granulomatosis with polyangiitis. Presentation of GPA at such an advanced age is rare, especially with the presentation at death.